Potujitveno prevajanje kulturnega besedja v romanu Smrt Artemia Cruza - Kastelic Vukadinović, Uršula (Ars et humanitas, 2017)
The paper discusses cultural words in the Slovenian translation of the novel The Death of Artemio Cruz by Carlos Fuentes. There are a number of cultural words in the analysed text that have no exact equivalents in other languages and cultures. These are also elements that contribute to the foreignization of the target text and show us the textual world as exotic and unknown. However, it is interesting that in a lot of cases the reader does not feel disoriented, because there are enough references in the text that he can understand what is needed. Moreover, the explanations in the footnotes help the reader a lot in those parts where the monologue of Artemio Cruz adopts an essayistic tone and the great questions about Mexico and the Mexicans arise. The reader thus has the feeling that he is losing himself in the whirlwind of Mexican history. These passages are difficult to understand (both in the original and the translation) due to the narrative techniques of the author and not so much to the realia. The translator of the studied text, Alenka Bole Vrabec, tends to choose the transfer of cultural words in order to retain some local colour, even when she could find equivalents in Slovenian or, at least, adapt the words to writing in accordance with the rules of the Slovenian language. These decisions accentuate the foreignizing character of the translation.
Keywords: Fuentes, Carlos: Smrt Artemia Cruza; kulturno besedje; literarni prevodi; potujevanje; prevajanje; slovenščina